Treatment of Sulphate Removal in Industrial Wastewater with By Using, Activated Charcoal Prepared from Sugarcane Waste - R.B., Shinde; Yogesh, Randhave; Shubham, Shinde; Abhiram, Kothimbire; Rahul, Pawar (International Journal of Scientific Research in Civil Engineering, 2020)
In this we are to remove out the sulphate content from the water as we know the sulphate is one of the very much dangerous Pollutant from the waste water which also have some salts and compounds which shows he carcinogenic properties and we know that the cancer cannot be cured at any stage of life,it is so much dangerous for which purpose If we use Activated charcoal prepared from the powder of the Sugarcane waste straws, stems, Dry leaves of a sugarcane with Hydrated lime, Alum, Aloe Vera then it is acts as good filter for all the pollutants from the water.
Keywords: Alum; Aloe Vera; Activated Charcoal; Hydrated Lime